Experiences of Fathers in Supporting Breastfeeding - Patcharin Ngoenthong (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2020)
Babies’ fathers can influence the breastfeeding behavior of new mothers. Thus, fathers' support is therefore very important for successful breastfeeding. The purpose of this qualitative research was to explore the experiences of fathers in supporting breastfeeding. Participants were 19 Thai fathers who were voluntarily recruited from the Health Promotion Center Region 1 and Well- Baby Clinic in Chiang Mai, Northern Thailand. The study period was from February 2018 to December 2019. Data were collected using face-to-face in-depth interviews and analyzed based on thematic analysis as established by Braun & Clark (2006). The findings showed that the fathers’ experience in supporting breastfeeding consisted of three themes: 1) Facing barriers to support breastfeeding, which included encountering difficulties with initial breastfeeding and having inadequate preparation to support breastfeeding; 2) Believing in the value of breastfeeding, which included understanding the benefits of breast milk and perceiving advantages of breastfeeding; and 3) Making an effort to continue breastfeeding, which included learning to support breastfeeding, dedicating oneself to support breastfeed, and seeking way to increase milk supply.The findings of this study provide insights about the thoughts, emotions, and practices from the experiences of fathers to support breastfeeding directly. This data can be used as basic information to improve nursing and midwifery practices, nursing education, and further nursing research.